2009
DOI: 10.1103/physrevb.80.174409
|View full text |Cite
|
Sign up to set email alerts
|

Quantum phase transition in(CuCl)La(Nb1xTax

Abstract: We demonstrate the synthesis and magnetic properties of a quasi-two-dimensional frustrated quantum spin system ͑CuCl͒La͑Nb 1−x Ta x ͒ 2 O 7 . We observed persistence of the spin-singlet state in ͑CuCl͒LaNb 2 O 7 up to x ϳ 0.4, accompanied by a slight reduction in the spin gap with increasing x. In spite of unaltered cell parameters and a preserved CuCl plane, ͑CuCl͒LaTa 2 O 7 exhibits collinear antiferromagnetic ͑CAF͒ order with T N ϳ 7 K as observed in ͑CuBr͒LaNb 2 O 7 . In the intermediate region ͑0.4Ͻ x Ͻ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 17 publications
2
28
2
Order By: Relevance
“…19,20 . X-ray diffraction results show no trace of impurity phases for the entire concentration regions 0 ≤ x ≤ 1 and 0 ≤ y ≤ 1 within the experimental detection limit.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 . X-ray diffraction results show no trace of impurity phases for the entire concentration regions 0 ≤ x ≤ 1 and 0 ≤ y ≤ 1 within the experimental detection limit.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Since then a few parallel efforts have been made in neutron scattering, high-field susceptibility / magnetization, NMR, and Raman scattering measurements. While NMR and Raman studies have been / will be reported in separate independent papers 17,18 µSR and the remaining studies and characterization of the specimens will be reported in three consecutive papers (I, II 20 and III 19 ). In this paper (I), we focus on µSR and low-field magnetic susceptibility measurements on Cu(Cl,Br)La(Nb,Ta) 2 O 7 , which demonstrate: (a) absence of static magnetism in (CuCl)LaNb 2 O 7 down to 15 mK confirming the spin-gapped ground state; (b) phase separation between partial volumes with a spin-gap and static magnetism in (CuCl)La(Nb,Ta) 2 O 7 ; (c) historydependent magnetization in the (Nb,Ta) and (Cl,Br) substitution systems; and (d) a uniform long-range collinear antiferromagnetic state in (CuBr)LaNb 2 O 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Contrasting behaviors are observed in the Nb-site substituted system, (CuCl)La(Nb1-yTay)2O7 (0 y 1) [40]. Reflecting similar ionic radii between Nb 5+ and Ta 5+ , the lattice parameters are almost constant with y.…”
Section: Cu(cl Br)la(nb Ta)2o7mentioning
confidence: 82%
“…Two kinds of solid solutions have been investigated, against Br-for-Cl [38,39] and Ta-forNb [39,40] substitution. For (CuCl1  xBrx)LaNb2O7 (0 x 1), the a-axis linearly increases with x, while the c-axis decreases.…”
Section: Cu(cl Br)la(nb Ta)2o7mentioning
confidence: 99%
See 1 more Smart Citation